PUBLIC RELATIONS AS A POWERFUL INSTRUMENT FOR BUSINESS GROWTH: THE ECONOMIC AND BRAND RECOGNITION INFLUENCE OF PUBLIC RELATIONS ON COMPANIES’ DEVELOPMENT (E Conference Zone, 2022)
This article explores the deconstruction of different levels of public relations, when and where PR is most commonly used, and whether PR technologies can effectively influence brand awareness and the economic status of a business.